Rudiments of a space security policy framework - Richard J. Chasdi (Centre for International Governance Innovation (CIGI), 2022)
The commercial space industry is taking off, with a growing number of private companies sending people into orbit. Along with this growth in demand from businesses and consumers is the need for more space security and policy approaches to address the potential risks of space exploration. The Moon is currently the main target of future space missions because of its resources and its strategic location to support missions to Mars. International law can help mitigate threats, such as resource depletion on the Moon, which could lead to conflicts among stakeholders on Earth.
Keywords: 330